LAW AND REGULATION IN EDUCATION MANAGEMENT - Hasibuan, Arfin; Hasibuan, Amanda; Daulay, Nur Gabena; Hasibuan, Nurliana (PERSPEKTIF: Journal of Social and Library Science, 2025)
Laws and regulations play a strategic role in shaping the direction, structure, and effectiveness of education management. Education is understood not only as a pedagogical process but also as an institutional practice within the framework of state administration and public policy. This article aims to analyze the role of laws and regulations in education management and identify challenges that arise in their implementation. This study uses a qualitative approach with a library research design, with data sources consisting of educational legislation, policy documents, academic books, and relevant journal articles. Data are analyzed using a juridical-normative approach and thematic analysis to interpret the function of regulations, implementation patterns, and their implications for education governance. The results of the study indicate that laws and regulations function as instruments of legitimacy, control, and direction in education management, particularly in ensuring accountability, quality standards, and legal certainty. However, this study also identified challenges in the form of gaps between norms and practices, regulatory rigidity, and policy inconsistencies between levels of government that have the potential to hinder innovation and managerial effectiveness. Therefore, a more adaptive, coherent, and evidence-based regulatory approach is needed so that the law does not only function as an administrative control tool, but also as a facilitator for improving the quality and sustainability of education management.